Surface tension and curvature energy of quark matter in the Nambu-Jona-Lasinio model - Lugones, G. (2013)
In this article we study the surface tension and the curvature energy of three-flavor quark matter in equilibrium under weak interactions within the Nambu-Jona-Lasinio model. We include the effect of color superconductivity and describe finite size effects within the multiple reflection expansion framework. Our calculations result in large values of the surface tension which disfavor the formation of mixed phases at the hadron-quark interphase inside a hybrid star.